Aplicação de ultrassom e etanol como pré-tratamento de secagem de fatias de banana e como método para extração de polifenóis das cascas - Granella, Suian José (2022)
Convection drying is one of the most relevant techniques for preserving and extending the shelf-life of agricultural products after harvest; however, numerous approaches and mechanisms occurring during the process should be better described. Applying pretreatments before drying could be an alternative to improve the bioactive and nutritional properties of plant materials and reduce drying time and energy consumption. Therefore, this work aimed to analyze the influence of different pretreatments (ultrasound and ethanol) on the drying of banana slices and the recovery of phenolic compounds from their peels. The fractional-order moisture diffusion model for drying banana slices was approached to understand this effect better. The results showed a process of super-diffusion of moisture during drying in the pretreated slices, an increase in drying speed, and a reduction in energy consumption. In addition, better quality retention was observed due to minor color change and retention of antioxidant activity. Similar results were obtained for the drying pretreatments applied to banana peels. In this case, they helped improve ultrasonic extraction performance in recovering phenolic compounds from pretreated banana peels. Furthermore, the ultrasonic parameters (temperature and ethanol concentration) were optimized, and an optimal point of 60.10% at 52.30 °C was obtained for maximum recovery of phenolic compounds, antioxidant activity, and extract yield. Extraction-assisted by ultrasound also achieved better results compared to traditional extraction techniques. The levels of phenolic compounds and flavonoids were also recovered in more significant amounts under the optimized ultrasonic extraction conditions compared to conventional extraction techniques. Finally, the current work is intended to contribute to the understanding of drying pretreatments to improve banana slices' quality and enhance the recovery performance of bioactive compounds from banana peels when using new extraction techniques.